Richard Patterson - Matters of life and death - Price, Matt; Sapera, Kat (Anomie, 2017)
Matters of Life and Death' is a limited-edition publication documenting the remarkable new and recent paintings of celebrated Dallas-based British artist Richard Patterson (b.1963). An engaging introduction by Paul Moorhouse, Senior Curator at the National Portrait Gallery, London, discusses the dynamic and complex relationship between figuration and abstraction in Patterson's oeuvre. Moorhouse observes: 'Visual ambiguity defines Patterson's art, and its most conspicuous feature is the interaction between figurative painting, abstraction and photography that his recent work continues. From the outset he moved between these disparate visual languages, combining them in ways that seemed deliberately oppositional and subversive.' Patterson's latest works are as provocative as ever, and as he enters mid-career, have become increasingly accomplished, cryptic and, at times, haunting
Keywords: Patterson, Richard -- 1963-; Malerei; Bildband